The Influence of Coretax System Implementation on Tax Evasion Behavior: Evidence from Taxpayer Data in Indonesia - Linting, Indriyanti (Accounting Profession Journal (APAJI), 2025)
Purpose – This study aims to systematically investigate the relationship between digital tax system implementation—particularly the Core Tax Administration System (Coretax)—and tax evasion behavior, with a focus on the Indonesian context. Design/methodology/approach – A Systematic Literature Review (SLR) was conducted following PRISMA guidelines. A total of 32 peer-reviewed articles published between 2010 and 2024 were analyzed from major databases, including Scopus, Web of Science, and ScienceDirect. The review applied thematic synthesis to extract dominant patterns, gaps, and theoretical perspectives related to digital tax reforms and tax evasion. Findings – The results indicate that digital tax systems significantly reduce tax evasion by enhancing transparency, real-time monitoring, and audit capacity. However, technical constraints, limited institutional readiness, and behavioral resistance—such as low digital literacy and perceived complexity—remain critical barriers. In Indonesia, evidence regarding the effectiveness of Coretax on tax evasion behavior is still limited, with most studies focusing on user perception rather than empirical compliance outcomes. Practical implications – To maximize the benefits of Coretax, policymakers must improve system infrastructure, enhance taxpayer support, and integrate behavioral insights into digital service design. Furthermore, empirical evaluations using actual taxpayer data are needed to assess the long-term impact of Coretax on tax compliance and evasion. Originality/value This study is among the first to systematically synthesize existing knowledge on digital tax reforms in developing countries with a focused lens on Indonesia’s Coretax system. It identifies theoretical, methodological, and practical gaps for future research and policy formulation.